Improving Local Governance in Angola : Strengthening the Links between Decentralization and Community Driven Development - Case Studies - World Bank (Washington, DC, 2013)
This study is the second phase of an analysis of local governance in Angola. The first phase aimed to identify factors enabling and constraining local governance, from the point of view of local government and of civil society. Phase one also identified opportunities for reinforcing state-citizen co-productive relationships. The second phase considers how current programs are dealing with the structural constraints and opportunities identified during phase one. The study aimed to be practice based and produce recommendations firmly based in local reality. The study is part of a three-country analysis by the World Bank, including the Philippines and Zambia, in addition to Angola. The three country studies followed the same questionnaire and gathered similar information to allow for comparative analysis. While the study highlights a variety of programs aimed at strengthening local government-civil society relationships, a note of caution is essential. Most of these programs are still in the relatively early stages and are continuing to identify the most effective approaches in overcoming constraints. Sustainability remains a live question for most and while the study tries to address this issue, further analysis will be required in the future.